2003
DOI: 10.1182/blood-2002-12-3722
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of canine cyclic neutropenia by lentivirus-mediated G-CSF delivery

Abstract: Cyclic neutropenia is a rare disease that occurs both in humans and gray collie dogs and is characterized by recurrent severe neutropenia leading to bacterial infections and shortened life expectancy. Daily injections of recombinant granulocyte colony-stimulating factor (rG-CSF) are effective in shortening the period of severe neutropenia and reducing infections. After demonstrating that rG-CSF induced elevated neutrophil production in an affected dog, cytokine administration was stopped and 10 9 infectious un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 51 publications
4
12
0
Order By: Relevance
“…This hypothesis was supported by the following observations: (a) lentiviral vectors have resulted in efficient in vivo gene transfer in hepatocytes, antigen-presenting cells, and muscle cells as well as cells in the central nervous system (16)(17)(18)(19)(20)(21); (b) intrathymic (IT) injection of a nonspecific lentiviral vector results in the transduction of thymic epithelial cells as well as a low number of immature thymocytes (22); (c) early T lymphoid progenitors (ETP) in the thymus appear to sustain production of T lineage progeny for longer periods of time than do the common lymphoid progenitors (CLPs) found in the BM (23). Thus we reasoned that IT injection of a T cell-specific lentiviral vector encoding a gene that provides a selective advantage for transduced prothymocytes might result in the generation of functional T lymphocyte progeny with subsequent long-term immune reconstitution.…”
Section: Introductionsupporting
confidence: 58%
“…This hypothesis was supported by the following observations: (a) lentiviral vectors have resulted in efficient in vivo gene transfer in hepatocytes, antigen-presenting cells, and muscle cells as well as cells in the central nervous system (16)(17)(18)(19)(20)(21); (b) intrathymic (IT) injection of a nonspecific lentiviral vector results in the transduction of thymic epithelial cells as well as a low number of immature thymocytes (22); (c) early T lymphoid progenitors (ETP) in the thymus appear to sustain production of T lineage progeny for longer periods of time than do the common lymphoid progenitors (CLPs) found in the BM (23). Thus we reasoned that IT injection of a T cell-specific lentiviral vector encoding a gene that provides a selective advantage for transduced prothymocytes might result in the generation of functional T lymphocyte progeny with subsequent long-term immune reconstitution.…”
Section: Introductionsupporting
confidence: 58%
“…34 Sustained exogenous treatment of dogs with G-CSF has been reported to cause EMH in dogs; however, this conclusion was based on finding increased numbers of neutrophils and bands in the spleen, which more likely reflected peripheral blood concentrations. 127 Marked accelerated thrombopoiesis. In humans, accelerated thrombopoiesis in the bone marrow as a response to immunemediated thrombocytopenia and increased thrombopoietin has been reported to result in secondary EMH (primarily megakaryocytopoiesis) in the spleen and other organs.…”
Section: Myelostimulation (Upregulation Of Medullary Hematopoiesis)mentioning
confidence: 99%
“…We have based the vectors described herein on the third generation self-inactivating lentiviral vectors first described and shared by Trono et al [10,43,44] and modified by us [12]. We, and others, have demonstrated that these lentiviral vectors have improved transduction efficiency, function and specificity, particularly into primary cells [45] and are also well tolerated in vivo [15,[46][47][48] making them ideal for in vivo studies. We chose to combine the shRNA and regulatory elements into a single vector as we felt that it is less practical to perform multiple transductions or to generate clones when targeting rare primary cells or using in vivo models.…”
Section: Discussionmentioning
confidence: 99%